SHIFT KERJA DENGAN KELELAHAN KERJA PETUGAS KEAMANAN DI PT PERTAMINA HULU MAHAKAM BALIKPAPAN - Saputri, Sri Retno; Mappangile, Andi Surayya; Zainul, L.M. (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
One of the main causes of work accidents caused by humans is fatigue. Causes of fatigue can be influenced by sleep disturbance due to jet lag or work shifts. The role of the security officer is to increase the feeling of security for employees at work. Therefore the security officer is demanded to always be at the worksite at all times. PT Pertamina Hulu Mahakam Balikpapan applies a shift system for security personnel consisting of the morning shift, afternoon shift and night shift. The purpose of this study was to determine the relationship of work shifts with work fatigue in security officers at PT Pertamina Hulu Mahakam Balikpapan. This research method uses quantitative using the IFRC (Industrial Fatigue Research Committee) questionnaire. IFRC (Industrial Fatigue Research Committee) questionnaire totalling 30 questions consisting of 10 questions about weakening activities, 10 questions about weakening motivation and 10 questions about depicting physical fatigue Sample selection is taken in total sampling where the number of samples is equal to the total population with 30 samples or respondent. Data analysis uses the Spearman rank to connect variables, the results of statistical calculations show a significant relationship if the dependent variable with the independent variable with a value of p (p-value) <a (0.05). The analysis showed that the morning shift felt tired by 15 people and not tired by 15 people, the afternoon shift felt tired by 14 people and not tired by 16 people and the night shift by feeling tired by 6 people and not tired by 16 people. From the Spearman rank test results obtained 0.017 (p <0.05), it was concluded that there is a relationship between work shifts with work fatigue.